The Effect Of Purple Sweet Potato Processed Product Innovation On The Nutritional Status And Hemoglobin Levels Of Pregnant Women In Mongeudong Village, Lhokseumawe City - Cut Linar; Muammar Muammar; Devi Aprianti; Wahyuni Wahyuni; Myrna Lestari AB; Hernita Hernita (CV. AFDIFAL MAJU BERKAH, 2026)
Food innovations based on local ingredients have the potential to improve the nutritional status and health of pregnant women. One of the local foods rich in nutrients is purple sweet potato, which contains complex carbohydrates, iron, and antioxidants. This study aims to analyze the effect of purple sweet potato product innovations on the nutritional status and hemoglobin levels of pregnant women in Mongeudong Village, Lhokseumawe City. This study used a quasi-experimental design with a pretest–posttest approach without a control group. The sample consisted of 34 pregnant women in their second and third trimesters selected using a total sampling technique. Nutritional status data were measured using BMI/MUI and hemoglobin levels were measured using a digital Hb device. Data analysis included univariate and bivariate analyses using paired t-tests. The results showed an increase in the nutritional status of pregnant women from 44.1% to 67.6% after the intervention. In addition, the proportion of pregnant women with normal hemoglobin levels increased from 41.2% to 70.6%. The statistical test results showed a significant effect of purple sweet potato product innovations on nutritional status (p = 0.002) and hemoglobin levels of pregnant women (p = 0.001). The conclusion of this study shows that the innovation of processed purple sweet potato products is effective in improving the nutritional status and hemoglobin levels of pregnant women